Application of steel spring on the ZnO nanorods self-powered triboelectric nanogenerator for efficient energy harvest in transformers - Simões, Agnes Nascimento (2021)
The demand for using wireless sensors to monitor gases dissolved in transformer oil is growing and has brought challenges in the development of new sources of energy. Nanogenerators are devices capable of converting mechanical energy, as vibrations, into electricity in a innovative and renewable way at low cost. In this work, the authors studied the addition of a steel spring to triboelectric nanogenerator (TENG) on the performance of its output power. Here, TENGs were built by using ZnO nanorods as donating electrons and PDMS:GO composites as negative material. PDMS:GO composites were prepared at different concentrations and the study was carried out in a wide frequency range (45 to 250 Hz). The addition of a steel spring to design of the TENG, as well as, 4% weight GO to PDMS improved the performance of the device. A power density around 246 mW m−2, and output voltage of 4 V were obtained at 60 Hz. TENG's ability to collect vibration energy from the wall of transformers and transform it into electrical energy is discussed based on the vibration frequencies obtained at different external points of transformers and performance of the devices.